Quality of life measurement in women with cervical cancer: implications for Chinese cervical cancer survivors - Zeng, Ying Chun (BioMed Central, 2010)
BACKGROUND: Women with cervical cancer now have relatively good 5-year survival rates. Better survival rates have driven the paradigm in cancer care from a medical illness model to a wellness model, which is concerned with the quality of women's lives as well as the length of survival. Thus, the assessment of quality of life among cervical cancer survivors is increasingly paramount for healthcare professionals. The purposes of this review were to describe existing validated quality of life instruments used in cervical cancer survivors, and to reveal the implications of quality of life measurement for Chinese cervical cancer survivors. METHODS: A literature search of five electronic databases was conducted using the terms cervical/cervix cancer, quality of life, survivors, survivorship, measurement, and instruments. Articles published in either English or Chinese from January 2000 to June 2009 were searched. Only those adopting an established quality of life instrument for use in cervical cancer survivors were included. RESULTS: A total of 11 validated multidimensional quality of life instruments were identified from 41 articles. These instruments could be classified into four categories: generic, cancer-specific, cancer site-specific and cancer survivor-specific instruments. With internal consistency varying from 0.68-0.99, the test-retest reliability ranged from 0.60-0.95 based on the test of the Pearson coefficient. One or more types of validity supported the construct validity. Although all these instruments met the minimum requirements of reliability and validity, the original versions of these instruments were mainly in English. CONCLUSION: Selection of an instrument should consider the purpose of investigation, take its psychometric properties into account, and consider the instrument's origin and comprehensiveness. As quality of life can be affected by culture, studies assessing the quality of life of cervical cancer survivors in China or other non-English speaking countries should choose or develop instruments relevant to their own cultural context. There is a need to develop a comprehensive quality of life instrument for Chinese cervical cancer survivors across the whole survivorship, including immediately after diagnosis and for short- (less than 5 years) and long-term (more than 5 years) survivorship.